Globular Adiponectin Inhibits Lipopolysaccharide-Primed Inflammasomes Activation in Macrophages via Autophagy Induction: The Critical Role of AMPK Signaling - Kim, Mi Jin (Int J Mol Sci, 2017)
The inflammasome acts as a key platform for the activation of pro-inflammatory cytokines. Adiponectin exhibits potent anti-inflammatory properties. However, the effect of adiponectin on the modulation of the inflammasome has not been explored. Herein, we show that globular adiponectin (gAcrp) suppressed lipopolysaccharide (LPS)-primed inflammasomes activation in murine peritoneal macrophages judged by prevention of interleukin-1β (IL-1β) maturation, caspase-1 activation, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) speck formation, and pyroptotic cell death. Interestingly, pretreatment with 3-methyl adenine, a pharmacological inhibitor of autophagy, abrogated the suppressive effects of gAcrp on IL-1β secretion and caspase-1 activation, indicating the crucial role of autophagy induction in gAcrp-modulation of the inflammasome activation. In addition, inhibition of 5′Adenosine monophaspahate (AMP)-activated protein kinase (AMPK) signaling abolished suppressive effect of gAcrp on inflammasomes activation. Furthermore, autophagy induction or inhibition of the inflammasome activation by gAcrp was not observed in macrophages deficient in AMPK. Taken together, these results indicate that adiponectin inhibits LPS-primed inflammasomes activation in macrophages via autophagy induction and AMPK signaling-dependent mechanisms.